Editorial (2008)
In memory of Professor Orlando Fals-Borda, who taught us the following: “It is possible to produce serious, responsible knowledge apt to accumulate through group vivencias and symmetrical information exchange…”1 As you might know, Professor Orlando Fals-Borda, promoter of participatory action research and founder of our Faculty of Human Sciences at Universidad Nacional de Colombia, passed away last August 12, in Bogotá. Hundreds of people came to our university to express their gratitude to an outstanding human being, sociologist and educator. Messages and notes were also written to portray his contributions and outstanding work. His lessons and ideas have had a great impact in our University and abroad.